Academic writing and grammar for students - Osmond, Alex (Sage study skills., 2013)
This clear and practical book on academic grammar shows students how to avoid common mistakes and how to quickly apply this to their essays. It is unique in its focus on English grammar for academic purposes across a range of disciplines.